1993
DOI: 10.1021/ma00060a041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of polyamides containing imidazole: intramolecular hydrogen bonding and constitutional isomerism

Abstract: Polyamides derived from l-methyl-4,5-imidazoledicarboxylic acid and aliphatic diamines such as hexamethylenediamine, neopentylenediamine, and ethylenediamine are synthesized and characterized.The polymers have inherent viscosities up to 0.56 dL/g, are amorphous, have good thermal stability, and are soluble in a wide range of solvents. The amide proton of the carboxamide at the 5-position of the imidazole intramolecularly hydrogen bonds to the carbonyl oxygen at the 4-position. There is little or no evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
13
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 2 publications
3
13
0
Order By: Relevance
“…The conformational behavior of bis-I45DCs having N-methyl imidazole rings has been described, 21 and we expect the bis-I45DCs in this study to be similar. We note that many of the bis-I45DCs show evidence of multiple conformations in both their 1 H and 13 C NMR spectra at room temperature.…”
supporting
confidence: 71%
“…The conformational behavior of bis-I45DCs having N-methyl imidazole rings has been described, 21 and we expect the bis-I45DCs in this study to be similar. We note that many of the bis-I45DCs show evidence of multiple conformations in both their 1 H and 13 C NMR spectra at room temperature.…”
supporting
confidence: 71%
“…Fig. 14 shows a selection of Rasmussen’s 4,5-dicyanoimidazole derivatives, such as vinazene 73 [ 29 , 81 ], push–pull amines and betaines 74 – 78 [ 82 – 87 ], alkoxy derivatives 79 , 80 [ 88 ], biimidazoles 81 [ 89 92 ], and triimidazoles 82 [ 93 94 ], as well as fullerenes [ 95 ] and polymers [ 96 99 ].…”
Section: Reviewmentioning
confidence: 99%
“…Variously 4,5-dicyanoimidazole-functionalized polymers were mainly investigated by Rasmussen et al [ 29 , 81 , 86 88 96 99 ]. However, these systems were not intended as nonlinear optical polymers.…”
Section: Reviewmentioning
confidence: 99%
“…Earlier work has shown that the I45DCs form a robust seven-membered intramolecular hydrogen bond in the solid state, along with a relatively small number of different intermolecular aggregation motifs . The solution conformation of I45DCs and other closely related analogues such as ring alkylated I45DCs has been previously reported. The torsional potential of the substituent amide bond of a ring alkylated I45DC was estimated to be worth 20 kcal/mol, a value that reflects the strength of this intramolecular hydrogen bond . Despite this interest in the intramolecular hydrogen-bonded conformation, no empirical determination of the hydrogen bond strength has ever been reported.…”
mentioning
confidence: 99%